Analisis Usability Aplikasi Sistem Informasi Destinasi Wisata Pulau Ambon Berbasis Android - Ginting, Sri Widyanti; Sudarma, I Made (Fakultas Ilmu Komputer, Universitas Brawijaya, 2020)
Pariwisata adalah berbagai macam kegiatan wisata dan didukung berbagai fasilitas serta layanan yang disediakan oleh seluruh elemen yang terkait. Ambon adalah daerah kepulauan yang memiliki panorama yang indah dengan objek wisata alam dan budayanya yang menarik. Keberadaan Teknologi mobile melalui perancangan aplikasi yang berisi fitur-fitur informatif tentang wisata Pulau Ambon berbasis Android sangat baik untuk digunakan. Untuk mengetahui respon pengguna terhadap aplikasi perlu dilakukan pengujian usability, agar diketahui kelebihan serta kelemahan aplikasi dan agar bisa meningkatkan performa aplikasi dimaksud. Penelitian dilakukan dengan menggunakan metode Waterfall dan hasil kuesioner yang diolah dengan menggunakan analisa Likert yang merupakan skala psikometrik yang paling banyak digunakan dalam riset berupa survey. Hasil penelitian menunjukkan bahwa sebagian besar responden setuju bahwa aplikasi sistem informasi destinasi wisata berbasis android mampu memenuhi learnability, eficiency, memorability, errors, dan satisfaction yang berarti cukup membantu pengguna dalam memperoleh informasi destinasi wisata di Pulau Ambon. AbstractThe research aims to determine the extent of Tourism Information Systems application on Ambon Island can be accepted by the public and the level of community satisfaction with the existing information system created. The author in this case creates an application to see the user's perception of the application of Android-based tourism information systems in Ambon City by relying on features that can be easily accessed with an easy display. Furthermore, to see the extent of the usability of the application, a test is performed to view the usability testing by involving the user, how users use the system and the problems the users experienced. The test was carried out using a questionnaire to measure user satisfaction and to observe the user's opinion of the application. The method used is the Waterfall method, which consists of Requirement Analysis, Design, Implementation, and Testing. Data collection was carried out by distributing written questionnaires to 100 respondents in several tourism spots. Questionnaire data given to respondents are analyzed using a Likert scale model. From the results diagram it can be analyzed that most respondents agree that the application is able to fulfill the usability components, which is learnability, efficiency, memorability, errors, and satisfaction. So it can be concluded that the Android-based Ambon Island tourism information system application is able to provide tourist attractions, tourist activities and culinary lists that can be used by tourists to facilitate them to plan their desired tourist destinations.